MANAJEMEN PERPUSTAKAAN SEKOLAH DASAR ISLAM TERPADU (SDIT) UMMUL QURO BOGOR - Nurul Khofifah; Maryanto; Ngurah Ayu N M (STKIP Subang, 2023)
School library management is basically a process of optimizing human, material, and budgetary contributions to achieve library goals. The purpose of this study is to describe the management of the Ummul Quro Bogor Integrated Islamic Elementary School (SDIT) Library, the specific purpose of which is to find out how the implementation of the management function in the Ummul Quro Bogor Integrated Islamic Elementary School (SDIT) Library starts from planning, organizing, implementing (actuating), controlling which is applied in the Ummul Quro Bogor Integrated Islamic Elementary School (SDIT) Library. This research method the author uses a descriptive research method with a qualitative approach to find out how the implementation of library management in the Ummul Quro Bogor Integrated Islamic Elementary School (SDIT) Library. The subject of this research is the head of the library, librarians, teachers, students and schools. The results of this study are the implementation of management functions in the Ummul Quro Bogor Integrated Islamic Elementary School (SDIT) Library has been implemented well.